Group Investigation Through Instagram in Public Speaking Class at STAI Hubbulwathan Duri: Case Study - Dini Deswarni; Muhammad Zaim (LPPM STKIP AL MAKSUM, 2023)
The purpose of this study is to look into the use of Group Investigation through Instagram as a public speaking learning sytartegy in the context of STAI Hubbulwathan Duri. The purpose of this case study is to investigate how the Group Investigation strategy is used in a public speaking class through Instagram, and how it affects students' learning outcomes and oral communication skills. The study intends to add to the existing literature on the effectiveness of Group Investigation as a learning method in the EFL context, particularly in developing students' speaking skills, as well as to investigate the potential of social media, specifically Instagram, as a tool to support language learning. The data took from interview and observation of the fourth semester students of English Department at STAI Hubbulwatahan Duri. The result showed the Group Investigation strategy was effective for English teaching, particularly for public speaking skills. The use of Instagram in the Group Investigation strategy provided an opportunity for students to easily share their views and engage in effective discussions while working together. Key words: Group Investigation, Instagram, Public Speaking.